Novel SEPN1 Mutations in Exon 1 Are Common in Rigid Spine With Muscular Dystrophy Type 1 in Chinese Patients - Fan, Yanbin; Xu, Zhifei; Li, Xing; Gao, Feng; Guo, Enyu; Chang, Xingzhi; Wei, Cuijie; Zhang, Cheng; Yu, Qing; Que, Chengli; Xiao, Jiangxi; Yan, Chuanzhu; et al. (Frontiers in Genetics, 2022)
Congenital muscular dystrophy with early rigid spine, also known as rigid spine with muscular dystrophy type 1 (RSMD1), is caused by SEPN1 mutation. We investigated the clinical manifestations, pathological features and genetic characteristics of 8 Chinese RSMD1 patients in order to improve its diagnosis and management. Eight patients presented with delayed motor development, muscle weakness, hypotonia, and a myopathic face, with high palatine arches. All patients could walk independently, though with poor running and jumping, and most had a rigid spine, lordosis or scoliosis. Symptoms of respiratory involvement were present early, and upper respiratory tract infections and pneumonia often occurred. Five patients had severe pneumonia, pulmonary hypertension, and respiratory failure. Lung function tests showed variable restrictive ventilation dysfunction. Polysomnography suggested hypoxia and hypoventilation. The serum creatine kinase (CK) level was normal or mildly increased. Muscle biopsy indicated chronic myopathic changes and minicores. Muscle magnetic resonance imaging (MRI) showed diffuse fatty infiltration of the gluteus maximus and thigh muscle. SEPN1 gene analysis revealed 16 compound heterozygous variants, 81.3% of which are unreported, including 7 exon 1 variants. Our study expands the spectrum of clinical and genetic findings in RSMD1 to improve diagnosis, management and standards of care. SEPN1 mutations in exon 1 are common and easily missed, and exon 1 should be carefully analyzed when RSMD1 is suspected, which will provide valuable genetic counseling for the family and useful information for future natural history studies and clinical trials.